Educação nas prisões do Estado de São Paulo: esforços históricos e os limites institucionais - Leme, José Antonio Gonçalves (2018)
This research investigates the educational practices developed in the prison units of the State of São Paulo and aims to discuss the institutional limits that interfere in the supply and quality of education in prisons. After the regulation of the National Guidelines for the Provision of Education in the Establishments of Criminal through Resolution no. 3, of march 11, 2009, the State of São Paulo, to conform to the new legislation, created the Education Program in Prisons, through Decree no. 57.238, 17 august 2011, which restructured the offer of education in Prisons. From this new reality, the educational activities in the interior of the prison units have gone through many changes, mainly with the inclusion of the State Department of Education as the main responsible for the organizing of the supply of Formal Education. By tracking the transformations that have occurred, the official data released, and the changes made little influenced in the educational actions on the interior of the prisons. Education in prisons must respect the principles and assumptions of Education for Young people and Adults and that, in addition to access, as a right, the quality of the actions should also be evaluated. The Investigation sought to verify, through data collection, information to explain the low rates of service, such as information that will contribute to an assessment of the actions that are being developed. Therefore, in addition to the analysis of the quantitative data available, the investigative process and provided the direct observation of activities such as conducting interviews with educators and students. The collected data show the institutional limits that interfere directly in the provision of education in prisons, providing elements that you can think of on the reorganization of public policies that have as a goal the inclusion and permanence of men and women in a situation of deprivation of liberty in Educational activities in the Prison